Editorial: Designing Spaces and Services in Contemporary Cities - Unanue, Mariane G. (International Journal of Architectural Engineering Technology, 2023)
Some questions accompany us very closely throughout our experiences and professional years. They may become a constant topic in our educational path, a gap to answer within research. Or they could become the lenses through which we glance and understand the world around us. According to Marina Waisman [1], the practice of architecture is based on relationships built from the conditions of a given time and place, and it is these conditions that will allow us to think and practice architecture reflectively and critically.